Trends in Research and Development (R&D) Using the Inquiry Model in Science Learning: A Systematic Literature Review - raudhatul jannah; Asrizal; Festiyed; Mega ELVIANASTI (ISER (Indonesian Science Education Research), 2026)
This study is a systematic literature review (SLR) that maps trends in research and development (R&D) using inquiry-based approaches in science learning. The review protocol was prepared a priori, and reporting follows PRISMA 2020, with procedures adapted from Kitchenham and Charters’ systematic review guidelines. In the context of 21st-century education and the growing use of digital learning, inquiry-based learning has been promoted as a way to cultivate higher-order thinking and scientific practices. The mapping synthesis draws on 43 eligible studies and shows that inquiry models are widely used to guide students in investigating problems through structured questioning, experimentation, and evidence-based reasoning.